Enhanced antigenicity of Nipah virus nucleocapsid protein displayed on hepatitis B core antigen - Yap, Wei Boon; Tey, Beng Ti; Mohammed Alitheen, Noorjahan Banu; Tan, Wen Siang (2012)
Display of the nucleocapsid protein (NP) of Nipah virus (NiV) on the hepatitis B core (HBc) particle enhances the antigenicity of the NP. In addition, the NP fused to the amino-teminus (NP401-532 HBc) and immunodominant loop of HBc (HBc79.80NP4O1'S31) was shown to be less sensitive to proteinase K. Some of the proteinase K treated NP401.32HBc and HBc79.80NP,O].s32 remained intact and antigenic. These results indicated two important implications, (1) the use of HBc virus -like particle as a carrier platform for foreign epitopes, (2 ) the use of NP401.532HBc as a diagnostic reagent for NiV infection.